Physicochemical and Photocatalytic Properties of Fe-Pillared Bentonite at Various Fe Content - Is Fatimah; Yuyun Yunani Nurkholifah (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2016)
Iron-pillared bentonites (Fe/Bents) were successfully prepared using a ferric chloride precursor. The prepared samples were characterized using XRD, BET and SEM-EDX. The results show that the pillared bentonite physicochemical character is affected by the iron content in a precursor solution. By Fe content variation it is found that Fe content in Fe/Bents is not linearly correlated with the specific surface area and the increased in d001 in which both the maximum specific surface are and d001 reach maximum at the Fe content of 20 mmol/g. Due to the kinetics of photocatalytic activity in phenol removal, it is concluded that in photo-Fenton-like processes.